Analysis of Fiber Metal Composite Shear Strength Using Independent Variables of Fiber Angle Orientation and Metal Surface Roughness - Hilmi Iman Firmansyah; wirawan wirawan; Moh Nasir Hariyanto (Polinema Press, Politeknik Negeri Malang, 2022)
Fiber Metal Laminates (FML) is a classification of metallic materials consisting of several thin layers of metal combined with composite materials. The constraint of FML is the weak bond between the layer material and the core composite. The weak bond between the layer material and the core composite can be influenced by several things, including the absence of an interlock system between the layer material and the core composite so that the strength of the FML composite decreases. In this study, a study was conducted on the shear strength of FML composites using the independent variables of surface roughness and fiber angle orientation. The highest shear strength in FML composite with fiber angle orientation of 45/45° and with a surface roughness value of 2.128 m with a shear strength value of 2.7 MPa